Pemberdayaan masyarakat melalui pembentukan kelompok tani sehat berbasis potensi lokal di Kelurahan Sialang Sakti, Kecamatan Tenayan Raya, Pekanbaru - Elda Nazriati; Sri Wahyuni; Herisiswanto Herisiswanto; Rofika Rofika; Zulharman Zulharman; Rita Endriani (Unri Conference Series: Community Engagement, 2020)
Cassava is one of the foodstuffs whose role is quite important in supporting the food security of a region, but the diversification of food made from cassava still needs to be improved. Health responsibility in the implementation of food security is carried out by compiling reference standards and technical health requirements throughout the food chain process, the principles of Sanitation Hygiene. Sialang Sakti is one of the sub-districts in Tenayan Raya District and is one of the potential cassava producing villages to be developed. The purpose of the service activities included ordering farmer groups that focus on the environment which also functions as a promotion forum for the Healthy Living Movement. Activities carried out in the form of advocacy to related parties, Focus Group Discussion (FGD), ordering farmer groups, trainings, and other activities to support efforts to promote the healthy community movement. The result of the activity was the formation of farmer groups that focus on cassava and health promotion, increased knowledge and skills of cassava cultivation, and the presence of appropriate technology products, and partnership with related parties.